Athlete satisfaction with a major multi-sport event: the importance of social and cultural aspects. Issue 2 (5th June 2017) - MacIntosh, Eric; Parent, Milena
Abstract : Purpose: In a major multi-sport event, the athlete is both a benefactor and producer of organizational activities. Athletes' centrality makes understanding their satisfaction with the event an important management activity. The purpose of this paper is to examine the lived athletes experience (during the event), so as to provide insight into the important Games facets contributing to their satisfaction and to explore the controllable aspects of the event from an organizer's perspective that athletes felt made the Games special and memorable. Design/methodology/approach: A multi-dimensional instrument (i.e. Athlete Experience Questionnaire) was designed and tested at previous iterations of a major multi-sport event and was employed during Games-time. In total, 813 athletes completed the questionnaire during the 2014 Glasgow Commonwealth Games. Findings: The findings demonstrated an overall high level of satisfaction with the event. Several important facets contributed to athlete satisfaction including social-, service- and communication-related aspects. Further, athletes reported on the importance of cultural opportunities within their Games experience. Research limitations/implications: The paper denotes the importance of the social and cultural interactions and opportunities which lie outside the athletes' actual competition experience and increase their specialness of the event. Theoretical and practical implications are drawn from the findings relative to the service-dominant logic and service-quality literature within a major multi-sport event Games for the athlete stakeholder. Originality/value: This paper explores how athletes experience the major international multi-sport event environment. Moreover, this paper offers a significant contribution from a hard-to-reach population (i.e. elite-level international athletes), adopts their perspective of the Games environment and determines what contributes to their satisfaction. As the authors highlight, the paper denotes the importance of the planned social and cultural interactions and opportunities, which lie outside the athlete's actual competition event experience, to increase athlete satisfaction; in contrast, basic sport competition needs seem to be a "basic" expectation.